Echinococcus granulosus Prevalence in Dogs in Southwest Nigeria - Oyeduntan Adejoju Adediran; Temitope Ubaidat Kolapo; Emmanuel Chibuike Uwalaka (Journal of Parasitology Research)
Echinococcosis is a public health parasitic disease that is cosmopolitan (Echinococcus granulosus) in its distribution. Domestic dogs (Canis familiaris) have been recognised as the definitive host of the parasite. The present study was carried out to determine the prevalence of canine echinococcosis in Southwest Nigeria using direct enzyme linked immunosorbent assay (ELISA) to detect sera antigen. Two hundred and seventy-three (273) canine sera were tested for the presence of Echinococcus antigen. Purpose of keeping (hunting or companion), age (young or adult), and sex of each dog were considered during sampling. Total prevalence recorded was 12.45% (34/273). There was significant difference (P<0.05) between hunting (15.94%) and companion dogs (1.52%) but there was no significant difference (P>0.05) between young and adult dogs. There was no association between sex and prevalence of canine echinococcosis. The result of this study established the presence of canine echinococcosis in Southwest Nigeria; thus there is the possibility of occurrence of zoonotic form of the disease (human cystic hydatid diseases) in the region.